Who is vulnerable in school? territorial relations between educational performance and socio–cultural context in the general pueyrredón district, argentina (2009)
One of the factors that allows to detect the location of population in educational vulnerability state of is the identification of relations between the households’ socio cultural characteristics and the students’ academic performance. From the analysis of this fact, the review and clarification of the concepts involved in it, using the data obtained by a Geographic Information System (GIS), this paper intends to show how educational vulnerability manifests in kids and teenagers in the General Pueyrredón district, province of Buenos Aires, Argentina. The methodology for the analysis is quantitative, since it is supported in a comparison of the Index of Socio-cultural Conditioning and the Index of Educational Performance (both in Z score). This work intends to evidence the spatial relations existing between social and cultural variables that configure the educational vulnerability map for the studied zone, which constitutes a highly relevant social topic.